2013
DOI: 10.4236/ns.2013.56090
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil of <i>Thymus vulgaris</i> L. and <i>Rosmarinus officinalis</i> L.: Gas chromatography-mass spectrometry analysis, cytotoxicity and antioxidant properties and antibacterial activities against foodborne pathogens

Abstract: The essential oil composition of Thymus vulgaris L. and Rosmarinus officinalis L. endemic to France were determined by GC and GC-MS. Oils were assessed for their cytotoxic, antioxidant and antimicrobial activity. 31 and 37 different compounds were identified representing 99.64% and 99.38% of the thyme and rosemary oils respectively, where oxygenated monoterpenes constituted the main chemical class. Thymol (41.33%) and 1.8-cineole (24.10%) were identified as the main constituents of T. vulgaris L. and R. offici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 40 publications
(58 reference statements)
6
34
2
1
Order By: Relevance
“…The higher antimicrobial activity of TEO could be attributed to its thymol content, a monoterpene with a phenolic ring (Miladi et al, 2013). However, the main component of REO and LEO is 1,8-cineole belonging to the ethers group (Celikel and Kavas, 2008;Miladi et al, 2013). Similar to our findings, Abdollahzadeh et al (2014) showed that TEO oil had a higher antimicrobial activity than REO against L. monocytogenes (PTCC 1163).…”
Section: Antimicrobial Activitysupporting
confidence: 81%
See 2 more Smart Citations
“…The higher antimicrobial activity of TEO could be attributed to its thymol content, a monoterpene with a phenolic ring (Miladi et al, 2013). However, the main component of REO and LEO is 1,8-cineole belonging to the ethers group (Celikel and Kavas, 2008;Miladi et al, 2013). Similar to our findings, Abdollahzadeh et al (2014) showed that TEO oil had a higher antimicrobial activity than REO against L. monocytogenes (PTCC 1163).…”
Section: Antimicrobial Activitysupporting
confidence: 81%
“…1, in general E. coli O157:H7 was less sensitive to the inhibitory activity of TEO, REO and LEO and their mixtures than S. aureus and L. monocytogenes. Generally, Gram-positive bacteria are known to be more susceptible to the essential oils or antibacterial compounds than Gram-negative bacteria, which are in a good agreement with previous findings (Miladi et al, 2013;Mith et al, 2014). This resistance could be attributed to the structure of cellular walls of Gram-negative bacteria, mainly with regard to the presence of lipoproteins and lipopolysaccharides that form a barrier to restrict entry of hydrophobic compounds (Mith et al, 2014).…”
Section: Dadalio¤lu and Akdemir Evrendileksupporting
confidence: 80%
See 1 more Smart Citation
“…In contrast, rosemary oil from cultivated plants from Mauritius did show tyrosinase inhibitory activity (median inhibitory concentration, IC 50 = 97 μg/mL) [101]. Rosemary oil was found to be relatively non-toxic to SK-OV-3, HO-8910, Bel-7402 (IC 50 ≥250 μg/mL) [102], MCF-7, LNCaP, and NIH-3T3 cells (IC 50 >180 μg/mL) [32], but active against A549 cells (IC 50 = 80 μg/mL) [103]. In summary, the enzyme inhibitory potential of rosemary oil is fairly low.…”
Section: Resultsmentioning
confidence: 99%
“…Imelouane et al, 13 Hajlaoui et al, 14 Zaouali et al, 15 Miladi et al 16 The research of these authors was used to compare the results obtained in this study. HDs have not been researched as extensively as EOs and their use in industry is much less important in spite of their important indirect production.…”
mentioning
confidence: 99%